Kepatuhan Pemberian Edukasi Kesehatan Gigi dan Mulut Oleh Mahasiswa Profesi Setelah Tindakan Perawatan Pada Pasien (Kajian Pada Pasien RSGM FKG Universitas Trisakti) - Andayani, Lia Hapsari; Juslily, Marta; Calvin, Christopher; Yusuf, Timotius William (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Dental health education is crucial for enhancing patient's knowledge and skills in maintaining oral health after treatment. Instructions from the operator aim to prevent complications and support healing. Patient compliance is influenced by their understanding and the effective delivery of information. Dental profession students are prepared to become professional dentist who are able to treat and educate patients well. Objective: To evaluate dental profession student’s compliance in giving post-treatment education at RSGM FKG Usakti. Methods: A descriptive observational study with a cross-sectional design was conducted through interviews in several clinics at RSGM FKG Usakti to assess dental profession student’s compliance in providing post-treatment dental health education. Results: Observations of 50 dental profession students and patients revealed high operator compliance: KII/KIH clinic 95.5%, KIG and KID 100%, and KIB 78.6%. Complete education was provided by 63.6% of operators at the KII/KIH Clinic, 85.7% at KIG and KID, and 57.1% at KIB. The use of easy-to-understand language was positively rated by most dental profession students. Conclusion: Dental health education is essential for improving post-treatment patient knowledge, with patient compliance influenced by clear understanding and effective information delivery.